Bifidobacterium longum Administration Diminishes Parasitemia and Inflammation During Plasmodium berghei Infection in Mice - Fitri LE; Sardjono TW; Winaris N; Pawestri AR; Endharti AT; Norahmawati E; Handayani D; Kurniawan SN; Azizah S; Alifia LI; Asiyah R; Ayuningtyas TR (Dove Medical Press, 2023)
Loeki Enggar Fitri,1,2 Teguh Wahju Sardjono,1,2 Nuning Winaris,1,2 Aulia Rahmi Pawestri,1,2 Agustina Tri Endharti,1 Eviana Norahmawati,3 Dian Handayani,4 Shahdevi Nandar Kurniawan,5 Syafiatul Azizah,6 Lustyafa Inassani Alifia,6,7 Rokhmatul Asiyah,6,8 Tita Rachma Ayuningtyas6 1Department of Parasitology, Faculty of Medicine, Universitas Brawijaya, Malang, Indonesia; 2AIDS, Toxoplasma, Opportunistic Disease, and Malaria (ATOM) Research Group, Faculty of Medicine, Universitas Brawijaya, Malang, Indonesia; 3Department of Anatomical Pathology, Dr. Saiful Anwar Hospital/Faculty of Medicine, Universitas Brawijaya, Malang, Indonesia; 4Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya, Malang, Indonesia; 5Department of Neurology, Faculty of Medicine, Universitas Brawijaya, Malang, Indonesia; 6Master Program in Biomedical Sciences, Faculty of Medicine, Universitas Brawijaya, Malang, Indonesia; 7Department of Parasitology, Faculty of Medicine, University of Muhammadiyah Malang, Malang, Indonesia; 8State University of Malang, Malang, IndonesiaCorrespondence: Teguh Wahju Sardjono, Department of Parasitology, Faculty of Medicine Universitas Brawijaya, Jl. Veteran, Malang, 65145, Indonesia, Tel +62 341 569117, Fax +62 341 564755, Email teguhws@ub.ac.idPurpose: During Plasmodium berghei (P. berghei) infection, infected erythrocytes are sequestered in gut tissues through microvascular circulation, leading to dysbiosis. This study aimed to investigate the effect of Lactobacillus casei (L. casei) and Bifidobacterium longum (B. longum) administration on the parasitemia level, gut microbiota composition, expression of cluster of differentiation 103 (CD103) in intestinal dendritic and T regulatory cells (T reg), plasma interferon gamma (IFN-γ) and tumor necrosis factor (TNF-α) levels in P. berghei infected mice.Methods: P. berghei was inoculated intraperitoneally. Infected mice were randomly divided into 5 groups and treated with either L. casei, B. longum, or the combination of both for 5 days before up to 6 days post-infection (p.i). The control group was treated with phosphate-buffered saline (PBS), while uninfected mice were used as negative control. Levels of CD103 and forkhead box P3 (FoxP3) expression were measured by direct immunofluorescense, while plasma IFN-γ and TNF-α level were determined using enzyme-linked immunosorbent assay (ELISA).Results: All treated groups showed an increase in parasitemia from day 2 to day 6 p.i, which was significant at day 2 p.i (p = 0.001), with the group receiving B. longum displaying the lowest degree of parasitemia. Significant reduction in plasma IFN-γ and TNF-α levels was observed in the group receiving B. longum (p = 0.022 and p = 0.026, respectively). The CD103 and FoxP3 expression was highest in the group receiving B. longum (p = 0.01 and p = 0.02, respectively).Conclusion: B. longum showed the best protective effect against Plasmodium infection by reducing the degree of parasitemia and modulating the gut immunity. This provides a basis for further research involving probiotic supplementation in immunity modulation of infectious diseases.Keywords: Bifidobacterium longum, inflammation, Plasmodium, sequestration